Polygonum minus: a tropical medicinal herb with vast applications in food, agricultural, and medicinal fields - Yang, Zhongming; Deng, Xi; Yang, Zhongguo; Han, Mingzhao; Ismail, Norsharina; Chan, Kim Wei; Abdull Razis, Ahmad Faizal; Mohd Esa, Norhaizan; Ho, Ket Li; Abu Bakar, Md Zuki (Elsevier, 2024)
Polygonum minus (PM) is a tropical medicinal herb that belongs to the family Polygonaceae, widely distributed in Southeast Asia, such as Malaysia, Indonesia, and Thailand. This herb has a sweet and pleasant aroma, commonly used as a flavoring agent. In addition, it is applied as a traditional medicine for multiple diseases, such as fungal infections, poor eyesight, and body aches. Due to its antioxidant and antimicrobial properties, PM is employed as a food additive for delaying or preventing the oxidation reaction of food and as an edible film for protecting food from microbiological contaminants. In livestock, poultry, and aquaculture industries, PM has been proposed as an alternative to traditional growth promoters with anti-parasitic properties. In respect of medicinal applications, PM has been proven to have protective effects on body systems and inhibitory effects on microbes. Moreover, nanotechnology has been applied to improve the efficacy and bioavailability of PM. This review aims to provide insight into the traditional uses, phytochemical properties, and toxicity, as well as applications of PM in food, agricultural, and medicinal fields.